Fluoropolymer ionomers with reduced catalyst poisoning and articles made therefrom

By using a composition of highly fluorinated ionomer and metal catalyst in the fuel cell electrode, the problem of catalyst poisoning caused by fluorinated ionic conductive polymers is solved, and the effect of improving catalytic activity and fuel cell performance is achieved.

CN113228356BActive Publication Date: 2025-03-253M INNOVATIVE PROPERTIES CO
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN201980082569.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-12-21
Filing Date
2019-10-25
Publication Date
2025-03-25
Estimated Expiration
2039-10-25

AI Technical Summary

Technical Problem

In hydrogen/oxygen fuel cells, fluorinated ion conductive polymers lead to catalyst poisoning and reduce catalytic activity.

Method used

Using a coating composition comprising a highly fluorinated ionomer and a metal catalyst, the ionomer has a polymer backbone and a suspended plurality of first side chains, the first side chains containing proton donor groups, and the first side chains between the polymer backbones are spaced at least 14 carbon atoms.

Benefits of technology

It effectively reduces catalyst poisoning, improves the catalytic activity of the electrode and the overall performance of the fuel cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113228356B_ABST
    Figure CN113228356B_ABST
Patent Text Reader

Abstract

A coating composition is described herein, the coating composition comprising: (a) a metal catalyst, wherein the metal catalyst comprises at least one of platinum, ruthenium, iridium, and alloys and combinations thereof; (b) an at least highly fluorinated ionomer, the at least highly fluorinated ionomer comprising a polymer backbone and a plurality of first side chains pendant from the polymer backbone, wherein the first side chains comprise at least one protogenic group, wherein the protogenic group is selected from sulfonic acid, bis(sulfonyl)imide, sulfonamide, sulfonyl methide, and salts and combinations thereof, and wherein the polymer backbone comprises an average of at least 14 carbon atoms between adjacent first side chains along the polymer backbone; and (c) a solvent. Such coating compositions can be used to prepare electrodes for electrochemical cells and have been shown to reduce catalyst poisoning.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention discloses a composition containing an electrode catalyst and a fluorinated ionomer and a product made therefrom, wherein the obtained electrode has reduced catalyst poisoning. Such an electrode can be used in an electrochemical device. Background Art

[0002] Electrochemical devices including proton exchange membrane fuel cells (PEMFCs), sensors, electrolyzers, chlor-alkali separation membranes, etc. have been constructed from membrane electrode assemblies (MEAs). Such MEAs typically include an ion-conducting membrane sandwiched between two electrodes (cathode and anode) to form a 3-layer MEA (also known as a catalyst-coated membrane or CCM). The ion-conducting membrane transports ions formed at one electrode to the other electrode, thereby allowing an electronic current to flow in an external circuit connecting the electrodes.

[0003] Hydrogen / oxygen fuel cell is a type of electrochemical device that produces electrical energy when supplied with hydrogen and oxygen. Hydrogen / oxygen fuel cell is usually formed by placing 3 layers of MEA between two porous conductive elements called gas diffusion layer (GDL) to form 5 layers of MEA. The typical 5 layers of MEA used in hydrogen / oxygen fuel cell can include a first GDL, a first electrode portion, an ion conductive membrane containing a proton exchange electrolyte, a second electrode portion and a second GDL. Such five layers of MEA can be used to generate electricity by the oxidation of hydrogen and the reduction of oxygen. In other embodiments, oxygen is provided by air. Summary of the invention

[0004] It is generally known that in hydrogen / oxygen fuel cells, fluorinated ion-conducting polymers reduce catalytic activity by "poisoning" the catalyst. Therefore, it is desirable to identify electrode compositions that reduce catalyst poisoning.

[0005] In one aspect, the use of a highly fluorinated ionomer for reducing poisoning of a metal catalyst in an electrochemical cell electrode is described, wherein the metal catalyst comprises at least one of platinum, ruthenium, iridium, and alloys and combinations thereof; and at least the highly fluorinated ionomer comprises a polymer backbone and a plurality of first side chains pendant from the polymer backbone, wherein the first side chains comprise at least one protogenic group, wherein the protogenic group is selected from sulfonic acids, bis(sulfonyl)imides, sulfonamides, sulfonyl methides, and salts and combinations thereof, and wherein the polymer backbone comprises an average of at least 14 carbon atoms between adjacent first side chains along the polymer backbone.

[0006] In another aspect, a coating composition is described. The composition comprises:

[0007] (a) a metal catalyst, wherein the metal catalyst comprises at least one of platinum, ruthenium, iridium, and alloys and combinations thereof;

[0008] (b) an at least highly fluorinated ionomer comprising a polymer backbone and a plurality of first side chains pendant from the polymer backbone, wherein the first side chains comprise at least one protogenic group, wherein the protogenic group is selected from the group consisting of sulfonic acids, bis(sulfonyl)imides, sulfonamides, sulfonyl methides, and salts and combinations thereof, and wherein the polymer backbone comprises an average of at least 14 carbon atoms between adjacent first side chains along the polymer backbone; and

[0009] (c) Solvent.

[0010] In another embodiment, an article is described, comprising a substrate having an electrode coating thereon, wherein the electrode coating comprises (a) a metal catalyst layer, wherein the metal catalyst layer comprises at least one of platinum, ruthenium, iridium, and alloys and combinations thereof; (b) an at least highly fluorinated ionomer layer, wherein the at least highly fluorinated ionomer layer comprises a polymer backbone and a plurality of first side chains pendant from the polymer backbone, wherein the first side chains comprise at least one of sulfonic acids, bis(sulfonyl)imides, sulfonamides, sulfonyl methides, and salts and combinations thereof, and wherein the polymer backbone comprises an average of at least 14 carbon atoms between adjacent first side chains along the polymer backbone.

[0011] In one embodiment, there is provided the use of the above-described article as a cathode in a fuel cell, wherein the catalyst is platinum. In another embodiment, there is provided the use of the above-described article as an anode in an electrolyzer, wherein the catalyst is substantially free of platinum.

[0012] The above summary of the invention is not intended to describe every embodiment. The details of one or more embodiments of the present invention are also listed in the following detailed description. Other features, objectives and advantages will be apparent from the description and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 is the equivalent weight of the -CF 2 -A graph showing the average number of protogenic groups. The graph shows a data point for a fluorinated ionomer with one protogenic group per side chain, two data points for a fluorinated ionomer with two protogenic groups per side chain, and extrapolated lines for ionomers with one protogenic group per side chain and two protogenic groups per side chain. A line roughly showing the position of an ionomer with three protogenic groups per side chain is also shown. DETAILED DESCRIPTION

[0014] As used herein, the term

[0015] “A,” “an,” and “the” are used interchangeably and refer to one or more; and

[0016] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B);

[0017] "Highly fluorinated" refers to a compound in which at least 75%, 80%, 85%, 90%, 95% or even 99% of the CH bonds are replaced by CF bonds, and the remainder of the CH bonds are selected from CH bonds, C-Cl bonds, C-Br bonds and combinations thereof;

[0018] "Perfluorinated" means a group or compound in which all carbon-hydrogen bonds have been replaced by carbon-fluorine bonds. Perfluorinated compounds may contain atoms other than fluorine and carbon atoms, such as oxygen, nitrogen, chlorine, bromine, and iodine atoms; and

[0019] For a chemical substance, "substituted" means substituted with conventional substituents that do not interfere with the desired product or process, for example, the substituents may be alkyl, alkoxy, aryl, phenyl, halogen (F, Cl, Br, I), cyano, nitro, etc.; and

[0020] "Discrete" refers to separate components with independent bodies, but does not exclude that the components are in contact with each other.

[0021] Also herein, ranges recited by endpoints include all numbers subsumed within that range (eg, 1 to 10 includes 1.4, 1.9, 2.33, 5.75, 9.98, etc.).

[0022] Moreover, as used herein, the expression "at least one" includes all numbers from one to greater than one (eg, at least 2, at least 4, at least 6, at least 8, at least 10, at least 25, at least 50, at least 100, etc.).

[0023] For example, for fuel cells, the cathode electrode is usually composed of an ion-conducting polymer (ionomer), a catalyst material (usually Pt and Pt-alloys) and a conductive material (carbon). In addition, the catalyst is usually dispersed on a conductive support such as carbon. In a typical PEMFC, oxygen is reduced on the cathode electrode side. Oxygen usually moves from the cathode flow field through the cathode GDL and enters the cathode electrode. Similarly, electrons are conducted through the cathode flow field, the cathode GDL and enter the cathode electrode. Protons move through the membrane into the cathode electrode. At each cathode catalyst site, protons, electrons and oxygen react to generate water. For this reaction, there is a reaction overpotential at the cathode, resulting in a loss of fuel cell efficiency. The greater the overpotential, the lower the operating efficiency of the cathode (and PEMFC). It is known that ionomers in the cathode contribute to the reaction overpotential and efficiency loss. In addition, it is known that ionomers "poison" the cathode catalyst metal, thereby generating additional efficiency losses in the cathode reaction and PEMFC. Therefore, materials that may reduce this catalyst poisoning, such as ionomers, will have great benefits for the electrochemical and fuel cell industries.

[0024] The present disclosure relates to coating compositions containing electrode catalysts and ionomers and articles made therefrom. Such coating compositions containing electrode catalysts and ionomers include a metal catalyst and at least a highly fluorinated ionomer, wherein the at least highly fluorinated ionomer is selected to reduce catalyst poisoning.

[0025] The ionomers disclosed herein are highly fluorinated or even perfluorinated and comprise multiple first side chains along the polymer backbone. Ideally, the ionomer is perfluorinated, however in some embodiments, the ionomer is highly fluorinated, comprises a C-H bond at the end of the polymer, wherein the polymerization reaction is initiated or terminated. These first side chains along the ionomer backbone comprise at least one protogenic group and at least one perfluorocarbon. Protogenic groups are groups that can contribute protons or hydrogen ions. Exemplary protogenic groups include: sulfonic acid, bis(sulfonyl)imide, sulfonamide, sulfonyl methide and their salts. If the first side chain comprises more than one protogenic group, these protogenic groups may be the same or different. In one embodiment, the ionomer comprises the same protogenic group. In another embodiment, the ionomer comprises different protogenic groups.

[0026] When these first side chains are spaced an average of at least 14, 16, or even 18 carbon atoms along the polymer backbone, reduced catalyst poisoning is observed compared to similar materials having proton donating side chains spaced an average of less than 14 carbon atoms. For example, the ionomers of the present disclosure have the following segments:

[0027]

[0028] Wherein "*" is the position where the segment is connected along the polymer backbone. The segment comprises two first side chains terminated by sulfonic acid groups. In the segment disclosed above, the two first side chains are separated by fourteen carbon atoms.

[0029] The first side chain comprises at least one perfluorocarbon, the at least one perfluorocarbon being intercalated with a protogenic group and / or being terminated by a protogenic group. In one embodiment, the first side chain comprises an average of at least 2, 4, or even 6 carbon atoms, and a maximum of 10, 12, 14, 16, 18, or even 20 carbon atoms, excluding carbons positioned along the polymer backbone. In one embodiment, the first side chain comprises at least one catenary heteroatom, such as oxygen (i.e., an ether bond).

[0030] The first side chain comprises at least one protogenic group. In one embodiment, the first side chain may comprise a plurality of protogenic groups, for example 2, 3 or 4 or more protogenic groups, such as a bis(perfluoroalkyl)sulfonimide terminated with a sulfonate. See, for example, U.S. Pat. No. 9,419,300 (Hamrock et al.) and U.S. Pat. No. 2017 / 0365870 (Schaberg et al.), both of which are incorporated herein by reference.

[0031] In one embodiment, the first side chain has the formula -O-(Rf)-SO 3 Y, wherein Rf is a divalent perfluorinated alkyl group which may be linear or branched and optionally contains at least one ether; and Y is H or a suitable counterion.

[0032] Exemplary proton donating first side chains include:

[0033] -O-(CF 2 ) m (OCF) n (CF 2 ) x SO 3 Y, wherein m is 2, 3, 4, 5 or 6; n is 0 or 1; x is 0 or 1;

[0034] -O-(CF 2 ) m -SO 3 Y, where m is 2, 3, 4, 5 or 6;

[0035] -O-(CF 2 CFCF 3 -O) x -CF 2 (CF 2 ) n -SO 3 Y, wherein x is 0, 1, 2 or 3; and n is 1, 2, 3 or 4;

[0036] -O-(CF 2 ) m -O-CF(CF 2 -SO 3 Y) 2 , where m is 2, 3, 4, 5 or 6;

[0037] -O-(CF 2 ) m -SO 2 NZ 2 , where m is 2, 3, 4, 5 or 6;

[0038] -O-(CF 2 ) m -SO 2 NZSO 2 -(CF 2 ) n -SO 3 Y, wherein m is 2, 3, 4, 5 or 6, and n is 2, 3, 4, 5 or 6;

[0039] -O-(CF 2 ) m -SO 2 NZSO 2 -(CF 2 ) n -SO 2 NH 2 , wherein m is 2, 3, 4, 5 or 6, and n is 2, 3, 4, 5 or 6;

[0040] -O-(CF 2 ) m -SO 2 NZSO 2 -(CF 2 ) p -SO 2 NZSO 2 -(CF 2 ) n -SO 3 Y, wherein m is 2, 3, 4, 5 or 6; p is 2, 3, 4, 5 or 6; and n is 2, 3, 4, 5 or 6;

[0041] -O-(CF 2 ) m -SO 2 NZSO 2 -(CF 2 ) p -SO 2 NZSO 2 -(CF 2 )x -CF 3 , wherein m is 2, 3, 4, 5 or 6; p is 2, 3, 4, 5 or 6; and x is 0, 1, 2, 3, 4, 5 or 6; and

[0042] -O-(CF 2 ) m -SO 2 NZSO 2 -(CF 2 ) x -CF 3 , wherein x is 0, 1, 2, 3, 4, 5 or 6, and m is 2, 3, 4, 5 or 6, and Y is independently selected from H and a suitable counter cation, and Z is independently selected from H and a suitable counter cation. Suitable counter cations include, for example, alkali metals such as lithium, sodium, potassium, etc.; alkaline earth metals such as calcium, magnesium, beryllium, etc.; and transition metals such as manganese. In one embodiment, the ionomer may include a plurality of second pendant side chains. These second side chains may be randomly positioned along the polymer backbone, even between adjacent first side chains, and are not proton donating. In one embodiment, the second side chains include at least one perfluorinated alkyl group (e.g., perfluorinated methyl), a perfluorinated alkyl ether (e.g., -O-(CF 2 ) x CF 3 , wherein x is 0 or 1), and / or perfluorinated alkyl polyether (e.g., -O-(CF 2 ) 3 -O-CF 3 ). In another embodiment, the ionomer is made by acidification of pendant sulfonyl fluoride groups of a perfluoropolymer. Thus, in one embodiment, these second side chains may comprise sulfonyl fluoride groups. In one embodiment, the ionomer comprising the first side chain and the second side chain has the following segments:

[0043]

[0044] Where "*" is the position where the segment is attached along the polymer backbone. The segment comprises two first side chains represented as wavy lines terminated by sulfonate ions and a second side chain of a perfluorinated methyl group. The wavy line represents an unspecified portion of the side chain. In the segment disclosed above, the two first side chains are separated by fourteen carbon atoms.

[0045] Ionomers are polymers. In one embodiment, the ionomer comprises at least 20, 50, 100, 500 or even 1000 repeating units.

[0046] Exemplary ionomers include: perfluorosulfonic acid (e.g., Nafion); perfluorosulfonyl imide-acid (PFIA); perfluoro-X-imide, where X can be, but is not limited to, methyl, butyl (PFBI), propyl, phenyl, etc.; and bis(sulfonyl)imides terminated with perfluorinated alkyl groups.

[0047] In one embodiment, the ionomer has a conductivity of at least 10, 20 or even 30 mS / cm and at most 50, 60, 70, 80, 80 or even 100 mS / cm at 50% relative humidity (RH) and 80°C.

[0048] Commercially available ionomers include, for example, those available under the trade designation “DYNEON” from 3M Company, St. Paul, MN; under the trade designation “NAFION” from DuPont Chemicals, Wilmington, DE; under the trade designation “FLEMION” from Asahi Glass Co., Ltd., Tokyo, Japan; under the trade designation “ACIPLEX” from Asahi Kasei Chemicals, Tokyo, Japan; and those available from ElectroChem, Inc., Woburn, MA, and Aldrich Chemical Co., Inc., Milwaukee, WI.

[0049] The metal catalyst includes at least one of platinum, ruthenium, iridium, and alloys and combinations thereof. The iridium may be an iridium-containing compound such as iridium oxide, IrO x, wherein x can be in the range of 0-2. Ruthenium can be a ruthenium-containing compound, such as ruthenium oxide. In one embodiment, the metal catalyst of platinum, ruthenium and / or iridium can be an alloy or intimate mixture with a metal, such as a transition metal (except Pt, Ir and Ru) composed of Group IV, Group VIb, Group VIIb and Group VIIIb. Exemplary metals include nickel, cobalt, hafnium, titanium, zirconium and manganese. Exemplary alloys include PtIr, PtRu, PtXIr, wherein X can be hafnium, titanium and zirconium. Exemplary metal catalysts include Pt+Ir, Pt+IrX, PtX+Ir, PtTi+Ir, PtX+IrY, wherein X can be gold, hafnium, titanium and zirconium, and Y is gold, hafnium, titanium and zirconium. In some embodiments, the atomic ratios of combined Pt, Ir, and Ru with other transition metals are 5:95 to 95:5, 10:90 to 90:10, 20:80 to 80:20, 30:70 to 70:30, or even 40:60 and 60:40. In some embodiments, the weight ratio of platinum to the total weight of iridium and / or ruthenium can be in the range of 1000: 1 to 1 : 1, 500: 1 to 1 : 1, 250: 1 to 1 : 1, 100: 1 to 1 : 1, 50: 1 to 1 : 1, 25: 1 to 1 : 1, 10: 1 to 1 : 1, 5: 1 to 1 : 1, 2.5: 1 to 1 : 1, 1000: 1 to 2.5: 1, 1000: 1 to 5: 1, 1000: 1 to 10: 1, 1000: 1 to 25: 1, 1000: 1 to 50: 1, 1000: 1 to 100: 1, 1000: 1 to 250: 1, 1000: 1 to 500: 1, and 10:3 to 4:3.

[0050] In one embodiment, the ratio of ionomer to catalyst is at least 0.01, 0.1, 1 or even 5 up to 10, 15 or even 20 parts by weight ionomer per 1 part by weight metal catalyst.

[0051] In one embodiment, the coating composition disclosed herein comprises additives. Such additives may include carriers such as carbon particles, needle-like particles, or metal organic framework structures; carbon particles and / or hydrophobic polymers.

[0052] In one embodiment, the metal catalyst is disposed on a support such as a needle-like particle or a metal organic framework structure. For example, the needle-like particle is a discrete elongated particle comprising a plurality of microstructured cores, wherein at least a portion of the surface of the microstructured core comprises a metal catalyst layer. Such needle-like particles and their configurations are known in the art, see, for example, U.S. Patents 5,338,430 (Parsonage et al.); 5,879,827 (Debe et al.); 5,879,828 (Debe et al.); 6,040,077 (Debe et al.); and 6,319,293 (Debe et al.); 6,136,412 (Spiewak et al.); and 6,482,763 (Haugen et al.), which are incorporated herein by reference.

[0053] In one embodiment, the metal catalyst is disposed on at least one surface (more preferably at least two or even three surfaces) of the plurality of microstructured cores. The metal catalyst is disposed on the entire surface in the form of a continuous layer so that electrons can continuously move from one part of the needle-like particles to another part of the needle-like particles.

[0054] In one embodiment, the thickness of the metal catalyst layer on the surface of the microstructured core can vary, but is typically in the range of at least 0.3 nm, 0.5 nm, 1 nm, or even 2 nm; and no greater than 5 nm, 10 nm, 20 nm, 40 nm, 60 nm, or even 100 nm on the sides of the microstructured core.

[0055] The carbon particles disclosed herein are those materials that comprise primarily (eg, greater than 90%, 95%, 99% by mole) elemental carbon in the bulk.

[0056] While not wanting to be bound by theory, it is believed that the carbon particles improve the conductivity of the metal catalyst; and additionally or alternatively, the carbon particles create pores that can enhance the transport of, for example, gases and water through the electrode.

[0057] Carbon particles can include amorphous carbon, crystalline carbon, graphitized carbon, and combinations thereof. Exemplary carbon includes elemental carbon, carbon black, acetylene black, graphite, graphene, graphitized carbon, carbon nanotubes, TKK F-type carbon, P-type carbon, graphitized Vulcan, graphitized carbon, and specialty carbon blacks, such as those purchased from Cabot Corp, Billerica, MA, under the trade name "VULCAN XC 72," and graphitized versions thereof; and those purchased from Akzo Nobel Chemicals Co., Amsterdam, Netherlands, under the trade name "KETJENBLACK EC-600JD," and graphitized versions thereof.

[0058] The scope of carbon particles useful in the present disclosure is not intended to be limited to the specific examples specified above, but is intended to include all available physical forms of carbon, such as powder, plates, rods, foams, felts, fibers, branched fibers, cloth, and the like.

[0059] In one embodiment, the carbon particles have an average major axis length of less than 100 nm, 75 nm or even 50 nm in diameter. In one embodiment, the carbon particles have an average major axis length of greater than 10 nm, 15 nm or even 20 nm, and less than 70 nm, 60 nm or even 50 nm.

[0060] In one embodiment, the ratio of carbon particles to acicular particles is from 1:100 to 100:1.

[0061] In one embodiment, the ratio of carbon particles to ionomer is from 5:1 to 0.1:1, more preferably from 2:1 to 0.5:1.

[0062] In one embodiment, noble metal-free (no Pt, Ir or Au) catalysts known as metal organic frameworks can be used with or without a carbon support. These catalysts are generally composed of an iron-nitrogen and carbon bonded framework structure.

[0063] In one embodiment, hydrophobic particles or polymers such as fluorinated polymers are added to the coating composition. Exemplary fluorinated polymers include: polytetrafluoroethylene; FEP (copolymer of hexafluoropropylene and tetrafluoroethylene); polyvinylidene fluoride; perfluoroalkoxy polymers; copolymers of ethylene and tetrafluoroethylene; copolymers of vinylidene fluoride, hexafluoroethylene and tetrafluoroethylene; and copolymers of tetrafluoroethylene and norbornene, such as those purchased from Chemours Co., Wilmington, DE under the trade name "TEFLON AF". In one embodiment, the ratio of hydrophobic particles or polymers to ionomers is 0.01:1 to 100:1, more preferably 0.01:1 to 2:1.

[0064] Typically, the metal catalyst is applied in the form of a dispersion, for example, as a spray, ink or paste, together with the ionomer, various solvents and optionally a carrier and / or a hydrophobic polymer.

[0065] In one embodiment, the ionomer and the metal catalyst (optionally including a support) are dispersed in a solvent. The solvent may include water, ketones (such as acetone, tetrahydrofuran, methyl ethyl ketone and cyclohexanone), alcohols (such as methanol, isopropanol, propanol, ethanol and propylene glycol butyl ether), polyols (such as glycerol and ethylene glycol); hydrocarbons (such as cyclohexane, heptane and octane), dimethyl sulfoxide and fluorinated solvents (such as heptadecafluorooctanesulfonic acid) and partially fluorinated or perfluorinated alkanes or tertiary amines (such as those available from 3M Co., St. Paul, MN under the trade name "3M NOVEC" or "3M FLUORINERT" liquids). In one embodiment, the coating composition is an aqueous dispersion, which optionally contains additional solvents and / or dispersants.

[0066] In one embodiment, the coating composition comprises 1 wt % to 40 wt % solids (ie, ionomer, metal catalyst, optional support, and optional hydrophobic polymer), and more typically 10 wt % to 25 wt % solids.

[0067] In one embodiment, the coating composition may include a low content of high boiling point solvents, such as those disclosed in U.S. Application 2009 / 0169949 (Hicks et al.), which is incorporated herein by reference. These solvents are high boiling point compounds having a boiling point greater than 120°C, 140°C, 160°C or even 180°C. Available high boiling point solvents may include non-fluorinated alkanes, olefins, amines, ethers or aromatic compounds that may be optionally substituted. Available high boiling point solvents may include partially fluorinated, highly fluorinated or fully fluorinated alkanes, olefins, amines, ethers or aromatic compounds that may be optionally substituted. Useful high boiling point solvents may include fluorinated solvents such as partially or fully fluorinated alkanes or tertiary amines, such as those available from 3M Company, St. Paul, Minnesota, under the trade name "3M NOVECENGINEERED FLUID" or "3M FLUORINERT ELECTRONIC LIQUID" or non-fluorinated ethers such as propylene glycol butyl ether. In some embodiments, the coating composition according to the present disclosure contains 0.1 wt%-50 wt%, more preferably 1 wt%-10 wt% of a high boiling point solvent.

[0068] In one embodiment, the coating composition disclosed above is applied to a substrate such as a polymer electrolyte membrane (PEM) or a gas diffusion layer (GDL); or a transfer substrate and subsequently transferred to a PEM or GDL to form, for example, an electrode.

[0069] PEM is known in the art. PEM can comprise any suitable polymer electrolyte. Polymer electrolyte usually carries anionic functional groups bonded to a common backbone, which are usually sulfate groups, but can also include carboxylic acid groups, imide groups, amide groups, bis(sulfonyl)imide, sulfonamide or other acidic functional groups. Polymer electrolytes are usually highly fluorinated, and most typically perfluorinated. Exemplary polymer electrolytes include those mentioned above for ionomers. Polymer electrolytes are usually cast into films (i.e., membranes) having a thickness of less than 50 microns, more usually less than 40 microns, more usually less than 30 microns, less than 25 microns in some embodiments, and about 15 microns in some embodiments. PEM can be composed of polymer electrolytes, or polymer electrolytes can be absorbed into porous carriers (such as PTFE). Examples of known PEMs include those available under the trade designation “NAFION PFSA MEMBRANES” from EI du Pont de Nemours and Co., Wilmington, DE; under the trade designation “GORESELECT MEMBRANE” from WL Gore & Associates, Inc., Newark, DE; under the trade designation “ACIPLEX” from Asahi Kasei Corp., Tokyo, Japan; and those from 3M Company.

[0070] GDL is also known in the art. Typically, GDL is a carbon fiber sheet selected from woven and non-woven carbon fiber constructions. Carbon fiber constructions that can be used in the practice of the present disclosure may include those available from Mitsubishi Rayon Corp. under the trade names "TORAY CARBON PAPER", "SPECTRACARB CARBON PAPER", "AFN" non-woven carbon cloth, "ZOLTEK CARBON CLOTH", carbon paper, etc. GDL can be coated or impregnated with various materials, including carbon particle coating, hydrophilic treatment and hydrophobic treatment, such as coating with polytetrafluoroethylene (PTFE).

[0071] Transfer substrate is a temporary carrier, which is not intended for the final use of the electrode, but is used to support and / or protect the electrode during manufacture or storage. The transfer substrate is removed from the electrode product before use. The transfer substrate includes a backing that is usually coated with a release coating. The electrode is arranged on the release coating, which allows the electrode to be easily and cleanly removed from the transfer substrate. Such transfer substrates are known in the art. The backing is usually composed of PTFE, polyimide, polyethylene terephthalate, polyethylene naphthalate (PEN), polyester and similar materials with or without a release coating.

[0072] Examples of stripping agents include carbamates or urethanes, silicones, fluorocarbons, fluorosilicones, and combinations thereof. Carbamate stripping agents typically have long side chains and relatively high softening points. An exemplary carbamate stripping agent is polyethylene octadecyl carbamate, available from Anderson Development Co. of Adrian, Mich., under the trade name "ESCOAT P20," and from Mayzo Inc. of Norcross, Ga., under various grades of RA-95H, RA-95HS, RA-155, and RA-585S.

[0073] Illustrative examples of surface-applied (i.e., topically applied) release agents include: polyvinyl urethanes, such as disclosed in U.S. Pat. No. 2,532,011 (Dahlquist et al.); reactive silicones; fluorinated polymers; epoxy silicones, such as disclosed in U.S. Pat. Nos. 4,313,988 (Bany et al.) and 4,482,687 (Kessel et al.); polyorganosiloxane-polyurea segmented copolymers, such as disclosed in European Application No. 250,248 (Leir et al.).

[0074] The organosilicon release agent generally comprises an organopolysiloxane polymer comprising at least two crosslinkable reactive groups, such as two ethylenically unsaturated organic groups. In some embodiments, the organosilicon polymer comprises two terminal crosslinkable groups, such as two terminal ethylenically unsaturated groups. In some embodiments, the organosilicon polymer comprises pendant functional groups, such as pendant ethylenically unsaturated organic groups. In some embodiments, the organosilicon polymer has a vinyl equivalent weight of not more than 20,000 g / equivalent, such as not more than 15,000 g / equivalent, or even not more than 10,000 g / equivalent. In some embodiments, the organosilicon polymer has a vinyl equivalent weight of at least 250 g / equivalent, such as at least 500 g / equivalent, or even at least 1000 g / equivalent. In some embodiments, the silicone polymer has a vinyl equivalent weight of 500 g / equivalent to 5000 g / equivalent, such as 750 g / equivalent to 4000 g / equivalent, or even 1000 g / equivalent to 3000 g / equivalent.

[0075] Commercially available silicone polymers include those available from Gelest Inc. under the trade designation "DMS-V", such as DMS-V05, DMS-V21, DMS-V22, DMS-V25, DMS-V31, and DMS-V33. Other commercially available silicone polymers containing an average of at least two ethylenically unsaturated organic groups include "SYL-OFF 2-7170" and "SYL-OFF 7850" (available from Dow Corning Corporation), "VMS-T11" and "SIT7900" (available from Gelest Inc.), "SILMER VIN 70", "SILMER VIN 100" and "SILMER VIN200" (available from Siltech Corporation), and 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane (available from Aldrich).

[0076] The stripping agent may also include a fluorosilicone polymer. Commercially available ethylenically unsaturated fluorosilicone polymers are available under the SYL-OFF series of trade names, including, for example, "SYL-OFF FOPS-7785" and "SYL-OFF FOPS-7786" from Dow Corning Corp. (Midland, Mich.) in Midland, Michigan. Other ethylenically unsaturated fluorosilicone polymers are commercially available from General Electric Co. (Albany, NY) and Wacker Chemie (Germany) in Albany, New York. Additionally available ethylenically unsaturated fluorosilicone polymers are described as component (e) in column 5, row 67 to column 7, row 27 of U.S. Patent 5,082,706 (Tangney). Fluorosilicone polymers are particularly useful in forming a stripping coating composition when mixed with a suitable crosslinking agent. One useful crosslinking agent is available from Dow Corning Corp. under the trade designation "SYL-OFF Q2-7560." Other useful crosslinking agents are disclosed in US Pat. Nos. 5,082,706 (Tangney) and 5,578,381 (Hamada et al.).

[0077] The coating composition can be initially mixed together in a spray, ink, paste or dispersion. Thus, the coating composition can then be applied to a PEM, GDL or transfer article in one or more layers, wherein each layer has the same composition or some layers have different compositions. Coating techniques known in the art can be used to apply the electrode composition to a substrate. Exemplary coating methods include knife coating, rod coating, gravure coating, spray coating, etc.

[0078] After coating, the coated substrate is typically dried to at least partially remove the solvent from the electrode composition, thereby leaving an electrode layer on the substrate.

[0079] Ionomers are used in coating compositions to prepare catalyst layers that can be used as electrodes in electrochemical cells. The electrodes are disposed between a membrane and its corresponding gas diffusion layer. In the case of a fuel cell, protons generated at the anode pass through the membrane, through the cathode and to the gas diffusion layer, where the protons react with hydrogen input to form water. Therefore, the electrodes must be able to move protons across the width of the electrode. The ionomers used in the electrodes act as a binder and enable the protons to conduct. Therefore, the ionomers should have a majority of ionic groups to enable this conduction. However, acids can poison metals such as platinum, thereby reducing their catalytic activity.

[0080] The catalyst coated PEM or catalyst coated GDL can be used in an electrochemical cell such as a fuel cell. Specifically, the catalyst composition of the present disclosure can be used, inter alia, in the anode portion of a hydrogen fuel cell.

[0081] In one embodiment of the present disclosure, a fuel cell assembly includes an anode electrode made from a composition of the present disclosure. MEA is a central element of a proton exchange membrane fuel cell such as a hydrogen fuel cell. A fuel cell is an electrochemical cell that produces usable electrical energy by catalytically combining a fuel (such as hydrogen) with an oxidant (such as oxygen). One face of the ion-conducting membrane is typically in contact with the anode electrode layer, and the opposite face is in contact with the cathode electrode layer. In typical use, hydrogen is fed to the anode side of the fuel cell, while air (oxygen source) is fed to the cathode side. During use, protons are formed at the anode by hydrogen oxidation. The protons are transported to the cathode through the ion-conducting membrane to react with oxygen, causing current to flow in an external circuit connecting the electrodes. The ion-conducting membrane forms a durable, non-porous, non-conductive mechanical barrier between the reactant gases, but it also easily transmits H + ions. The gas diffusion layer (GDL) facilitates the transport of reactants and product water to and from the anode and cathode electrode materials and conducts current. The GDL is both porous and conductive, and is typically composed of carbon fibers. The GDL may also be referred to as a fluid transport layer or a diffuser / current collector. In some embodiments, the anode and cathode electrode layers are applied to the GDL to form a catalyst-coated backing layer (CCB), and the resulting CCB is sandwiched in the PEM to form a five-layer MEA. The five layers of the five-layer MEA are, in order: anode GDL, anode electrode layer, PEM, cathode electrode layer, and cathode GDL. In other embodiments, the anode and cathode electrode layers are applied to either side of the PEM, and the resulting catalyst-coated membrane (CCM) is sandwiched between two GDLs to form a five-layer MEA. In operation, the five-layer MEA is positioned between two flow field plates to form an assembly, and in some embodiments, more than one assembly is stacked together to form a fuel cell stack.

[0082] In one embodiment, the coating compositions disclosed herein comprise platinum and can be used as cathodes in fuel cell applications. In another embodiment, the coating compositions disclosed herein comprise iridium and can be used as anodes in electrolyzer applications.

[0083] In typical operation, a fuel cell generates electricity when supplied with a fuel such as hydrogen and an oxidant such as oxygen from the air. Hydrogen is reduced to hydrogen ions and electrons at the positive electrode. The electrons provide an electric current to drive an external load, and the hydrogen ions pass through the membrane. At the negative electrode, oxygen combines with the hydrogen ions to form water as a byproduct. The operation of the fuel cell depends on the degree of transmission of gases, liquids, electrons, and ions through the materials forming the MEA layers. The durability of the fuel cell depends on the selection of materials and the accumulation in the MEA in a manner that prevents degradation or loss of key components such as catalyst area and efficiency, prevents carbon oxidation and corrosion, and prevents ionomer degradation.

[0084] Typically, the cathode contains pores for gas transport, a catalyst and optional carbon for electron transport, and an ionomer for proton transport. The types and amounts of these components are optimized to achieve high performance. Ionomers are known to affect the performance of catalysts to varying degrees.

[0085] This effect can be seen in Table 2 of the Examples section, where various ionomers have different activity losses. Figure 1 The average number of -CF2- units between the first side chains is plotted against the equivalent weight of the ionomer. The data points correspond to each embodiment or comparative example run, and ΔV (dV or activity loss) is reported for each data point. The dotted lines are marked and represent the position to which the ionomer with 1 protogenic group per side chain will tend, the position to which the ionomer with two protogenic groups per side chain will tend, and the position to which the ionomer with three protogenic groups per side chain will tend. It is also known that ionomers with lower equivalent weights (in other words, more protogenic groups per molecular weight) make the ionomer more ionically conductive, which is generally advantageous. Therefore, when considering membranes for electrochemical cells, ionomers with lower equivalent weights are generally preferred. When considering ionomers for use in electrodes, a balance must be struck between the conductivity of the ionomer and the activity of the catalyst. As clearly shown in the figure, ionomers having more than 14 carbon atoms between the first side chains have reduced activity loss in the catalyst compared to ionomers having an average of less than 14 carbon atoms between the first side chains along the polymer backbone.

[0086] While not wanting to be limited by theory, it is believed that having an average of at least 14 (at least 16 or even 18) carbon atoms between two adjacent first side chains is responsible for the reduced catalyst poisoning compared to the same highly fluorinated ionomer having an average of less than 14 carbon atoms between two adjacent first side chains. Generally, the average carbon number does not exceed 18, 20, 22 or even 24 carbon atoms attached between two adjacent first side chains to ensure that the ionomer has adequate conductivity.

[0087] The equivalent weight (EW) of an ionomer refers to the weight of the ionomer that will neutralize one equivalent of base. For two ionomers having the same average repeat unit molecular weight calculated from the molar ratio of the incorporated monomers, the ionomer with the lower equivalent weight will have more protogenic groups than the ionomer with the higher equivalent weight. For example, a 1- to 2-hydroxy-1-nitropropene ionomer having 4 protogenic groups derived from TFE (CF 2 =CF 2 ) monomer unit and 1 derived from CF 2 =CFOC 4 F 8 SO 3 A polymer with a repeating unit of monomer units of H will have a structure similar to that of 1.09 monomer units derived from TFE and 1 monomer unit derived from CF. 2 =CFOC 4 F 8 SO 2 NHSO 2 C 3 F 6 SO 3 The polymers made from the monomer units of CF H have the same average molecular weight of repeating units (780 g / mol). 2 =CFOC 4 F 8 SO 2 NHSO 2 C 3 F 6 SO 3 H has two proton-donating groups, so it is similar to using CF 2 =CFOC 4 F 8 SO 3 The polymer prepared by H (780 g / mol H + ) compared to CF 2 =CFOC 4 F 8 SO 2 NHSO 2 C 3 F 6 SO 3 The equivalent weight of the polymer prepared by H will be 390 g / mol H +. Traditionally, lower equivalent weight ionomers are more desirable because in the electrode, they will generally contain more protogenic groups / volume and therefore be able to conduct more protons, potentially leading to more efficient operation. However, increasing the protogenic concentration and / or lower equivalent weight can be produced by different methods. The first is to reduce the spacing or number of carbon groups between the side chains containing a single protogenic group. The second is to increase the number of protogenic groups per side chain. By the second method, the EW can be maintained or even reduced while increasing the distance (number of carbon groups) between the protogenic side chains. In the present disclosure, it has been found that ionomers with further spaced side chains (containing more carbon groups between the side chains) are more ideal for electrode catalyst compositions to prevent catalyst poisoning.

[0088] For optimal performance as an electrode, the ionomer used in the electrode should fall within Figure 1 In the lower right quadrant of , i.e., there is a gain in conductivity and activity. In one embodiment, the equivalent weight of the ionomer is at least 600, 700, 750 or even 800; and not more than about 1000, 1200 or even 1500. In one embodiment, the ionomer has an equivalent weight of at least 350 g / mol and less than 928 g / mol. However, the equivalent weight may depend on the protogenic groups in each side chain. For example, in one embodiment, the ionomer comprises at least one bis(sulfonyl)imide, and the ionomer has an equivalent weight of at least 350 g / mol and at most 1100 g / mol. In another embodiment, the ionomer comprises at least one sulfonic acid or a salt of a sulfonic acid, and the ionomer has an equivalent weight of at least 1100 g / mol and at most 1500 g / mol.

[0089] Exemplary embodiments include, but are not limited to, the following embodiments:

[0090] Embodiment 1: Use of highly fluorinated ionomers for reducing metal catalyst poisoning in electrochemical cell electrodes, wherein the metal catalyst comprises at least one of platinum, ruthenium, iridium, and alloys and combinations thereof; and at least the highly fluorinated ionomer comprises a polymer backbone and a plurality of first side chains suspended from the polymer backbone, wherein the first side chains comprise at least one protogenic group, wherein the protogenic group is selected from sulfonic acid, bis(sulfonyl)imide, sulfonamide, sulfonyl methide, and salts and combinations thereof, and wherein the polymer backbone comprises an average of at least 14 carbon atoms between adjacent first side chains along the polymer backbone.

[0091] Embodiment 2: The use according to embodiment 1, wherein the first side chain comprises at least two proton donating groups.

[0092] Embodiment 3: The use according to embodiment 1, wherein the first side chain is -O-(Rf)-SO 3 Y, wherein Rf is a divalent perfluorinated alkyl group, optionally containing at least one ether; and Y is H or a suitable counterion.

[0093] Embodiment 4: The use according to embodiment 3, wherein the first side chain is -O-(CF 2 ) m -SO 3 Y, wherein m is 2, 3, 4, 5 or 6, and Y is H or a suitable counterion.

[0094] Embodiment 5: The use according to embodiment 3, wherein the first side chain is -O-[CF 2 CF(CF 3 )O] x -CF 2 -[CF 2 ] y -SO 3 Y, wherein x is 0-3; y is 1-4; and Y is H or a suitable counterion.

[0095] Embodiment 6: The use according to any one of embodiments 1 to 3, wherein the first side chain is -O-(CF 2 ) m -O-CF-[CF 2 SO 3 Y] 2 , wherein m is 2, 3, 4, 5 or 6; and Y is H or a suitable counterion.

[0096] Embodiment seven: The use according to any one of the preceding embodiments, wherein the at least highly fluorinated ionomer has an equivalent weight of less than 928 g / mol.

[0097] Embodiment Eight: The use according to any one of the preceding embodiments, wherein the at least highly fluorinated ionomer has an ionic conductivity of at most 100 mS / cm at 50% relative humidity and 80°C.

[0098] Embodiment Nine: The use according to any one of the preceding embodiments, wherein the at least highly fluorinated ionomer comprises at least one bis(sulfonyl)imide and the at least highly fluorinated ionomer has an equivalent weight of at least 350 g / mol.

[0099] Embodiment 10: The use according to any one of embodiments 1 to 8, wherein the at least highly fluorinated ionomer comprises at least one sulfonic acid or a salt of a sulfonic acid, and the at least highly fluorinated ionomer has an equivalent weight of at least 1100 g / mol.

[0100] Embodiment eleven: The use according to any one of the preceding embodiments, wherein the at least highly fluorinated ionomer comprises at least one second side chain, wherein the second side chain is not proton donating.

[0101] Embodiment 12: The use according to embodiment 11, wherein the second side chain comprises at least one of a perfluorinated alkyl ether, a perfluorinated alkyl polyether and a perfluorinated alkyl group.

[0102] Embodiment 13: The use according to any one of the preceding embodiments, wherein the metal catalyst is disposed on a carrier.

[0103] Embodiment 14: The use according to Embodiment 13, wherein the carrier is at least one of carbon particles, needle-shaped particles and metal organic framework structures.

[0104] Embodiment 15: The use according to any one of the preceding embodiments, wherein the mass ratio of the at least highly fluorinated ionomer to the metal catalyst is at least 0.01 to at most 20.

[0105] Embodiment 16: A coating composition, the coating composition comprising:

[0106] (a) a metal catalyst, wherein the metal catalyst comprises at least one of platinum, ruthenium, iridium, and alloys and combinations thereof;

[0107] (b) an at least highly fluorinated ionomer comprising a polymer backbone and a plurality of first side chains pendant from the polymer backbone, wherein the first side chains comprise at least one protogenic group, wherein the protogenic group is selected from the group consisting of sulfonic acids, bis(sulfonyl)imides, sulfonamides, sulfonyl methides, and salts and combinations thereof, and wherein the polymer backbone comprises an average of at least 14 carbon atoms between adjacent first side chains along the polymer backbone; and

[0108] (c) Solvent.

[0109] Embodiment 17: The composition according to embodiment 16, wherein the first side chain comprises at least two protogenic groups.

[0110] Embodiment 18: The composition according to Embodiment 16, wherein the first side chain is -O-(Rf)-SO 3 Y, wherein Rf is a divalent perfluorinated alkyl group, optionally containing at least one ether; and Y is H or a suitable counterion.

[0111] Embodiment 19: The composition according to embodiment 18, wherein the first side chain is -O-(CF 2 ) m -SO 3 Y, wherein m is 2, 3, 4, 5 or 6, and Y is H or a suitable counterion.

[0112] Embodiment 20: The composition according to embodiment 18, wherein the first side chain is -O-[CF 2 CF(CF 3 )O] x -CF 2 -[CF 2 ] y -SO 3 Y, wherein x is 0-3; y is 1-4; and Y is H or a suitable counterion.

[0113] Embodiment 21: A composition according to any one of embodiments 16 to 17, wherein the first side chain is -O-(CF 2 ) m -O-CF-[CF 2 SO 3 Y] 2 , wherein m is 2, 3, 4, 5 or 6; and Y is H or a suitable counterion.

[0114] Embodiment 22: The composition of any one of Embodiments 16 to 21, wherein the at least highly fluorinated ionomer has an equivalent weight of less than 928 g / mol.

[0115] Embodiment 23: The composition of any one of Embodiments 16 to 22, wherein the at least highly fluorinated ionomer has an ionic conductivity of at most 100 mS / cm at 50% relative humidity and 80°C.

[0116] Embodiment 24: A composition according to any one of Embodiments 16 to 17 and 22 to 23, wherein the at least highly fluorinated ionomer comprises at least one bis(sulfonyl)imide and the at least highly fluorinated ionomer has an equivalent weight of at least 350 g / mol.

[0117] Embodiment 25: A composition according to any one of Embodiments 16 to 23, wherein the at least highly fluorinated ionomer comprises at least one sulfonic acid or a salt of a sulfonic acid, and the at least highly fluorinated ionomer has an equivalent weight of at least 1100 g / mol.

[0118] Embodiment 26: The composition of any one of Embodiments 16 to 25, wherein the at least highly fluorinated ionomer comprises at least one second side chain, wherein the second side chain is not proton donating.

[0119] Embodiment 27: The composition of embodiment 26, wherein the second side chain comprises at least one of a perfluorinated alkyl ether, a perfluorinated alkyl polyether, and a perfluorinated alkyl group.

[0120] Embodiment 28: The composition according to any one of Embodiments 16 to 27, wherein the metal catalyst is disposed on a support.

[0121] Embodiment 29: The composition according to Embodiment 28, wherein the carrier is at least one of carbon particles, needle-shaped particles and metal organic framework structures.

[0122] Embodiment 30: The composition of any one of Embodiments 16 to 29, wherein the composition comprises a mass ratio of the at least highly fluorinated ionomer to the metal catalyst of at least 0.01 to at most 20.

[0123] Embodiment 31: The composition according to any one of Embodiments 16 to 30, wherein the composition further comprises an additive.

[0124] Embodiment 32: A composition according to Embodiment 31, wherein the additive is at least one of carbon particles, needle-shaped particles and metal organic framework structures.

[0125] Embodiment 33: The composition according to any one of Embodiments 16 to 32, wherein the solvent comprises at least one of an alcohol, a polyol, a ketone, water, a fluorinated solvent, and a combination thereof.

[0126] Embodiment 34: The composition of any one of Embodiments 16 to 33, wherein the composition comprises 1 wt % to 40 wt % solids.

[0127] Embodiment 35: An article comprising a substrate having an electrode coating thereon, wherein the electrode coating comprises

[0128] (a) a metal catalyst phase, wherein the metal catalyst phase comprises at least one of platinum, ruthenium, iridium, and alloys and combinations thereof; and

[0129] (b) at least a highly fluorinated ionomer layer, the at least highly fluorinated ionomer layer comprising a polymer backbone and a plurality of first side chains pendant from the polymer backbone, wherein the first side chains comprise at least one of a sulfonic acid, a bis(sulfonyl)imide, a sulfonamide, a sulfonyl methide, and salts thereof, and combinations thereof, and wherein the polymer backbone comprises an average of at least 14 carbon atoms between adjacent first side chains along the polymer backbone.

[0130] Embodiment Thirty-six: The article of Embodiment Thirty-five, wherein the substrate is a gas diffusion layer, a gasket, or an ion-conducting membrane.

[0131] Embodiment Thirty-Seven: The article of any one of Embodiments Thirty-Five to Thirty-Six, wherein the electrode coating has a thickness of at least 0.1 micrometers and at most 100 micrometers.

[0132] Embodiment 38: Use of the article according to any one of Embodiments 35 to 37 as a cathode in a fuel cell, wherein the catalyst comprises platinum.

[0133] Embodiment 39: Use of the article according to any one of Embodiments 35 to 37 as an anode in an electrolytic cell, wherein the catalyst is substantially free of platinum.

[0134] Example

[0135] Unless otherwise indicated, all parts, percentages, ratios, etc. in the examples and the rest of the specification are by weight, and all reagents used in the examples are obtained or purchased from common chemical suppliers, such as, for example, Sigma-Aldrich Company, Saint Louis, Missouri, or can be synthesized by conventional methods.

[0136] These abbreviations are used in the following examples: A = ampere, cm = centimeter, g = gram, °C = degrees Celsius, RH = relative humidity, mA = milliampere, mol = mole, sccm = standard cubic centimeter per minute, and V = volts.

[0137] Table 1: Materials

[0138]

[0139]

[0140] Membrane preparation for ionic conductivity testing :

[0141] Films of PFSA-725 were prepared by dispersing an ionomer powder (available from 3M under the trade designation "725EW PFSA ionomer") at about 33% solids in an ethanol / water solvent mixture of about 75% ethanol / 25% water by mixing the ionomer and solvent in a bottle that was slowly rolled overnight to obtain a uniform dispersion. The films were prepared by casting the dispersion onto a 2 mil (51 micrometer) thick polyimide film (available from DuPont, Wilmington, DE, under the trade designation "KAPTON") on a glass substrate using a 4 inch (10 cm) wide microfilm applicator (available from Paul N. Gardner Company, Inc., Pompano Beach, FL) with a wet gap thickness of 8 mils (200 micrometers) that was uniform over the 4 inch width of the coating. The wet coating was dried in a forced air oven at 120°C under an aluminum pan cover for 30 minutes. The coated polyimide was transferred from the glass substrate to an aluminum substrate with an aluminum pan cover and heated to 140°C for 15 minutes and raised to 160°C for annealing and held for 10 minutes to produce a 30 micron thick proton exchange membrane. The membrane was removed from the polyimide and titrated according to the following method.

[0142] Films of PFSA-825, PFSA-1200, PFIA-620, and PFIA-814 were prepared following the above procedure except that the solvent system and polymer solids of the dispersion were as shown in Table 2. Coating thickness and drying and annealing temperatures were as disclosed in the table if different.

[0143] Table 12: Preparation of membranes for ionic conductivity measurements

[0144]

[0145] Table 3

[0146] Ionomer Name Equivalent weight (g / mol) Dry thickness (micrometer) PFSA-725 ~725 30 PFSA-825 ~825 24 PFSA-1000 ~1000 56 PFSA-1200 ~1200 38 PFIA-620 620 22 PFIA-814 814 30

[0147] PFSA-1000 membrane preparation

[0148] Membranes or films of PFSA-1000 (a 1000 g / mol equivalent weight perfluorosulfonic acid ionomer of the type described in U.S. Pat. No. 7,348,088) were prepared from a dispersion of the ionomer in a solvent and polymer solids as described in Table 1. The ionomer solution was coated at a constant flow rate onto a 2 mil (51 micron) polyimide liner (KAPTON, available from DuPont, Wilmington, DE) using a coating die and a line speed of about 1 meter per minute, with a target dry thickness of 30 microns, using a pilot coater manufactured by Hirano Entec Ltd., Nara, Japan, with four drying zones arranged in series in the longitudinal direction of the web and set at 50° C., 100° C., 120° C., and 145° C., respectively. The membrane was then subjected to a second heat treatment at the temperature described in Table 1.

[0149] Titration of membranes (EW measurements)

[0150] A 20-60 micron thick and approximately 0.5-0.6 g of acid-form ionomer membrane was dried at 120°C for 20 minutes, weighed, and added to 50 g of 1 M NaCl (aq.). The membrane was allowed to ion exchange over 4 hours with gentle agitation by rolling or shaking the bottle. A 20 mL aliquot of the NaCl (aq.) solution containing the generated HCl was titrated with 0.1 M - 0.03 M NaOH to determine the ion exchange capacity of a known mass of membrane.

[0151] Bulk membrane proton conductivity test method :

[0152] The films produced above were measured using a standard in-plane 4-point probe conductivity device with platinum electrodes. The cells were electrically connected to a potentiostat (Model 273, Princeton Applied Research, Oak Ridge, Tenn.) and an impedance / gain phase analyzer (SI 1260, Schlumberger). AC impedance measurements were performed using ZPLOT and ZVIEW software (Scribner Associates Inc., Southern Pines, NC). Temperature and relative humidity (RH) were controlled using a constant humidity oven (Model 1000H, obtained from Test Equity, Moorpark, CA). In this test method, an initial condition of 70% RH (relative humidity) with a set temperature of 80°C was selected, and then the %RH was gradually reduced to 25% RH and then gradually increased back to 90% RH. Each condition was maintained for 90 minutes. The test results are included below.

[0153] Rotating Disk Electrode (RDE) Procedure

[0154] Experimental Procedure for Ionomer / Catalyst Interaction Studies Using RDE

[0155] All references to deionized (DI) water refer to ultrapure (18.2 Mohm) water (GenPure UV-TOC xCADplus, Thermo Scientific, Waltham MA). Unless otherwise indicated, all potentials given are relative to a reversible hydrogen electrode (RHE).

[0156] All chemicals were used as received. Perchloric acid solutions were prepared from Veritas double distilled 70% reagent (GFS Chemicals, Powell, OH) and measured directly into perfluoroalkoxyalkane (PFA) containers (Savillex, Eden Prairie MN) to minimize contamination during transfer. Ionomer solutions were prepared with 99.99995% NN-dimethylformamide (DMF) purchased under the trade name TRACESELECT (FLUKA, Honeywell Specialty Chemicals Seelze GmbH, Seelze, Germany) and HPLC / spectrophotometric grade 200 normal strength ethanol (Sigma-Aldrich, St. Louis, MO).

[0157] Glassware and solution preparation. All experimental glassware used in the electrochemical cell was first cleaned with an aqueous solution (0.5 mass %) of Alconox (Alconox Inc., White Plains NY) detergent to remove contaminants and rinsed thoroughly with DI water. The glassware was then immersed in a bath of 96% sulfuric acid (Sigma-Aldrich) for a period of 24 hours. The glassware was then transferred to a sulfuric acid bath with a glassware cleaner obtained under the trade name NOCHROMIX (Godax Laboratories, Bethesda, MD) and kept fully immersed for 24 hours. The NOCHROMIX solution was prepared by dissolving one commercial bag with 2.5 L of 96% sulfuric acid. The glassware was then transferred to a DI bath and kept fully immersed for 24 hours to rinse off the sulfuric acid. This step was repeated once more with fresh DI water. After rinsing, the glassware was transferred to a DI water bath and rigorously boiled for 8 hours each six times over a period of one week. The DI water was replaced between each boiling step. In addition to these pre-cleaning steps, the glassware was boiled in fresh DI water for at least 8 hours between experiments.

[0158] RDE Electrode Cleaning. Polycrystalline platinum (Pt-Poly) RDE electrodes (5.0 mm disk diameter, 15.0 mm diameter PEEK cover, Pine Research Instrumentation, Durham, NC) were cleaned on 8" diameter MicroCloth polishing pads (Buehler, Lake Bluff IL) via a two-step mechanical polishing process: first step for 60 seconds using 0.05 μm alumina polishing compound (Buehler), and second step for 60 seconds without polishing compound. In both steps, the MicroCloth pad was first wetted with DI water. After each mechanical polish, the electrode was thoroughly rinsed with DI water for 60 seconds. After mechanical polishing, the electrode was mounted on a spinner and immersed in a 0.1 M HClO 4 The electrochemical cell uses ultra-high purity (99.999%) N 2 (Oxygen Service Company, Saint Paul, MN) for 30 min. The potential was then cycled for at least 30 min (about 66 full cycles) between 0.04 V and 1.4 V vs. RHE (reference hydrogen electrode) at a scan rate of 100 mV / s and an electrode rotation rate of 1600 rpm (revolutions per minute) while constantly bubbling N 2 To electrochemically clean the electrodes.

[0159] Preparation and coating of ionomer solutions. A 20 wt % aqueous solution of dimethylformamide (DMF) was prepared for use as a dilution solvent. The ionomer solution was prepared by dissolving the selected ionomer powder in 75:25 (wt %) ethanol:water to form a 1 wt % mother solution. The 1 wt % mother solution was then used to form a dilute (0.0075 wt %) solution using a 20 wt % DMF solution as solvent. All solutions (mother solutions and dilutions) were thoroughly mixed on a drum for 24 hours before use.

[0160] After electrochemical cleaning, the ionomer was spotted onto the Pt-Poly electrode to form a continuous film. 15 μl of 0.0075 wt % ionomer in DMF / H2O was added by a microliter pipette. 2 O solution was dropped onto the surface. The electrode was then transferred to an oven and 2 The ionomer solvent was removed by drying at 80 °C for 20 min under an atmosphere. The oven temperature was then steadily increased to 120 °C over 20 min to improve the mechanical stability of the ionomer membrane. The density of the PFSA ionomer was assumed to be 1.5 g / cm 3 , the resulting film thickness is calculated to be approximately 40 nm.

[0161] Electrochemical characterization

[0162] The electrochemical reaction was performed using custom electrochemical glassware fabricated in-house by 3M in 0.1 M HClO 4 Electrochemical surface area (ECSA) and oxygen reduction reaction (ORR) experiments were performed to characterize the electrodes. 2 / Pt electrode, so that the capillary end is ∼1 cm below the RDE electrode, which serves as the reference electrode. The reference electrode is designed so that ultra-high purity H 2 A constant stream of gas was bubbled over the surface of a coiled 0.3 mm diameter x 10 cm long Pt wire (Alfa Aesar, Tewksbury MA). The capillary tip was made as small as possible to minimize H 2 Penetration into the cell. A 25×25 mm woven Pt mesh (0.34 mm thick) and a 10 cm long 0.6 mm diameter Pt wire (Alfa Aesar) were used as counter electrodes. An Autolab PGSTAT302M potentiostat (Metrohm Autolab, Herisau, Switzerland) with FRA32M (impedance spectroscopy) and SCAN250 (analog scanning) modules was used for all electrochemical measurements.

[0163] After a 30-min electrochemical cleaning procedure, 2 ECSA scans were performed using cyclic voltammetry (CV) without rotation under the cover. The initial potential was +0.3 V and the device was scanned in the anodic direction to +1.4 V, followed by a cathodic scan at 50 mV / s to +0.04 V. This cycle was repeated three times. A specific charge of 210 microcoulombs / cm was assumed. 2 Pt , the final scan data is used to scan H through the cathode 2 The surface area was calculated by integrating the underpotential deposition area.

[0164] After ECSA characterization, ORR scan was performed using linear sweep voltammetry (LSV). 2 A background scan was performed at 20 mV / s from -0.01 V to +1.0 V at 1600 RPM under the overlay with iR compensation turned off. The gas was changed to O 2 , and the solution was bubbled through the frit for 7 minutes to ensure complete oxidation. The valve on the glassware apparatus was then switched to form O 2The overlay was placed over the solution to measure the uncompensated resistance of the solution. The iR compensation value was calculated by performing the Autolab hardware current interruption technique at a potential of 0.2 V, where the ORR current is in the current limiting regime. Current interruption measurements were performed by applying a constant potential and then triggering the current interruption circuit while measuring the potential decay. Based on the measured potential decay, the uncompensated resistance value (R u ). Perform three consecutive interrupt measurements and take the average of the obtained linear regression values ​​(R 平均 ). Immediately after the current interruption technique, repeat the 1600RPM LSV scan from -0.01V to +1.0V at 20mV / s using the same conditions as the background scan, except that iR compensation is turned on. Set iR compensation to 0.95*R 平均 After completing the LSV scan, switch the gas back to N 2 The bubbles were allowed to bubble through the frit for at least 10 minutes before proceeding to the next experiment (usually repeated using a second electrode).

[0165] Measuring the Activity Effects of Ionomer Powders :

[0166] In order to compare the catalyst mass activity in the presence of different ionomers, the voltage at a specific current measured using a bare Pt-Poly electrode is compared with the voltage obtained at the same current after the electrode is coated with an ionomer. The data is obtained during the LSV (linear sweep voltammetry) scan as described above. The specific current to be used is determined by taking the limiting current (the maximum current between +0.2V and +0.6V, where the ORR current is limited by mass transport) and multiplying by 0.5. The measured voltage difference corresponding to the 1 / 2 limiting current between the bare scan and the ionomer-coated scan is expressed as ΔV. In all cases, the original voltage obtained at the 1 / 2 limiting current is in a kinetic state, where the ORR current is not limited by mass transport, but by the kinetics of the reduction reaction. It is in this region that the effect of the ionomer coating becomes apparent, and is therefore used as a sufficient analog of actual fuel cell performance. Typically, the voltage is between +0.8 and +0.9V relative to RHE.

[0167] Comparative Example 1 (CE1)

[0168] A rotating disk electrode was prepared using a perfluorosulfonic acid (PFSA) polymer having an equivalent weight of 725 g / mol as the selected ionomer powder for measurements as described above in the rotating disk electrode (RDE) procedure. This material had an average of 7.9 -CF2- units between monomers containing proton donating side chains, as shown in Table 2. Activity loss was measured by the method described above in the section on measuring the activity of ionomer powders. Four samples were measured and the results were averaged.

[0169] Comparative Example 2 (CE2)

[0170] The test was carried out as in Comparative Example 1, except that the ionomer powder was a PFSA having an equivalent weight of 825 g / mol. Four samples were measured and the average was taken. The material had an average of 9.9 -CF2- units between the monomers containing proton donating side chains.

[0171] Comparative Example 3 (CE3)

[0172] The test was carried out as in Comparative Example 1, except that the ionomer powder was a PFSA having an equivalent weight of 1000 g / mol. Four samples were measured and the average was taken. The material had an average of 13.4 -CF2- units between the monomers containing proton donating side chains.

[0173] Comparative Example 4 (CE4)

[0174] The test was performed as in Comparative Example 1, except that the ionomer powder was a perfluoroimidic acid (PFIA) having an equivalent weight of 620 g / mol, synthesized from a sulfonyl fluoride precursor of 800 g / mol. Four samples were measured and the average was taken. The material had an average of 9.4 -CF2- units between the monomers containing the proton donating side chains.

[0175] Example 1 (E1)

[0176] The test was carried out as in Comparative Example 1, except that the ionomer powder was a PFSA having an equivalent weight of 1200 g / mol. Two samples were measured and the average was taken. The material had an average of 17.4 -CF2- units between the monomers containing proton donating side chains.

[0177] Example 2 (E2)

[0178] The test was carried out as in Comparative Example 1, except that the ionomer powder was a PFSA having an equivalent weight of 1500 g / mol. Four samples were measured and the average was taken. The material had an average of 23.4 -CF2- units between the monomers containing proton donating side chains.

[0179] Example 3 (E3)

[0180] The test was performed as in Comparative Example 1, except that the ionomer powder was PFIA having an equivalent weight of 814 g / mol, synthesized from a sulfonyl fluoride precursor of 1100 g / mol. Two samples were measured and the average was taken. The material had an average of 15.4 -CF2- units between the monomers containing proton donating side chains.

[0181] As shown in Table 4 below, the average number of -CF2- units between the first side chains, the equivalent weight of the ionomer, its activity loss, and the conductivity of CE1-CE4 and E1-E3 at 50% RH and 90% RH are shown.

[0182] Table 4: Ionomers used as examples and comparative examples

[0183]

[0184] NM means not measured

[0185] Comparison of ionomers in fuel cell cathodes

[0186] Cathode catalyst mass activity was measured in two essentially identical hydrogen fuel cells, except that the ionomer in one cathode electrode was PFSA-825 and the other was PFSA-1200.

[0187] Catalyst quality activity test program

[0188] Each ionomer was incorporated into the cathode of a fuel cell as described in more detail below. The cell temperature was set to 80°C and the inlet gas was humidified to 100% RH. The initial gas flow rate was 800 sccm H 2 (anode) and 1800 sccm N 2 (cathode), and the cell was kept open circuit for 5 minutes. The cathode gas was switched to O 2 , and 1A / cm 2 The battery was then charged at 0.01, 0.02, 0.03, 0.05, 0.075, 0.10, 0.125 and 0.150 A / cm 2 Measure the voltage for 15 seconds at a current density of 0.20, 0.25, 0.30A / cm 2 The current density was 0.40, 0.50, 0.70 and 1.0 A / cm2 for 30 seconds. At this point, the high frequency resistor (HFR) was turned on to measure the resistance loss of the membrane to the anode / membrane and cathode / membrane interfaces. The impedance between 10 Hz and 10,000 Hz was measured and the 0 intercept value was obtained on the real axis. In the same way, the impedance was measured at 0.40, 0.50, 0.70 and 1.0 A / cm2. 2 The voltage and HFR resistance value at each point were measured for 60 seconds.

[0189] Then by first averaging between 0.40 and 1.0 A / cm 2 The second step is to adjust all voltages to remove the resistance loss for the HFR values ​​between 0.01A / cm and 1.0A / cm 2 All measured voltages are regulated between:

[0190] V[without IR] = V[measured at each specific current density] + HFR[Ω*cm 2 ]*Current density [A / cm 2 ].

[0191] Once V[no IR] vs. current density is obtained, determine the current density at which V[no IR] crosses 0.9 V. Divide this value by the areal loading (mg Pt / cm 2 ) to obtain the final mass activity in A / mgPt.

[0192] Table 5: Fuel cell structure

[0193]

[0194] General electrochemical cell structure

[0195] All tests described below were performed in the same electrochemical cell using the same type of ion exchange membrane and anode configuration. The cathode configuration was varied in each specific example or comparative example as described below.

[0196] Anode catalyst layer veneer preparation

[0197] A dispersed catalyst ink composition containing carbon-supported catalyst 10EA50E and PFSA-825 ionomer was prepared. The ratio of the amount of ionomer to carbon in the catalyst was 8 / 10. The catalyst ink solution was coated on the silicone side of a silicone-coated polyethylene terephthalate (PET) release liner film using a Mayer rod and then dried at 130° C. for 10 minutes to form a cathode catalyst layer overlay.

[0198] Catalyst coated membrane (CCM) preparation

[0199] The ionomer membrane was placed between the anode catalyst layer facing and cathode catalyst layer facing prepared above (as described in the Comparative Examples and Examples below), with the liner on the outside of the construction and the catalyst facing the ionomer membrane. The construction was hot roll laminated using a 6 foot (15.2 cm) diameter heated steel roller heated to 325°F (163°C) at a roll speed of 1.2 feet per minute (0.37 m / s), with the rollers compressed together with a force of 625 pounds per linear inch (110 kilograms per linear centimeter), calculated by the width of the ionomer membrane. The silicone coated PET release liner was removed from the construction immediately after lamination to form the CCM.

[0200] Assembling a single cell fuel test station

[0201] The CCM is installed between two GDLs and placed directly 50cm 2 A single fuel cell (trade name "50CM 2CELLHARDWARE" (50SCH) was obtained from Fuel Cell Technologies, Albuquerque, NM) with a square spiral graphite flow field and gaskets selected to compress the gas diffusion layer by 10%. After assembly, the test cell was connected to a test station (obtained from Fuel Cell Technologies, Inc. under the trade designation "SINGLE FUEL CELL TESTSTATION"). Hydrogen was provided to the anode side and air was provided to the cathode side. The test station was used to control the applied cell voltage or current density, hydrogen and air pressures, flow rates and water vapor content (relative humidity), and test cell temperature.

[0202] Electrochemical Cell Testing Procedure

[0203] Battery Conditioning

[0204] After assembling the test cell and connecting it to the test station, each CCM was subjected to a conditioning or "break-in" period prior to performance testing. A hydrogen flow was connected to the anode side of the test cell, and air was connected to the cathode side of the test cell. The test cell was maintained at 60°C and 100% relative humidity for a hydrogen flow rate of 800 sccm and an air flow rate of 1800 sccm. 2 Potentiodynamic sweeps of the cell voltage from 0.9 V to 0.3 V were run repeatedly until a steady-state power output was reached.

[0205] Comparative Example 5

[0206] The cathode veneer was prepared by forming a dispersed catalyst ink composition comprising a carbon-supported catalyst 10V50E and a PFSA-825 ionomer. The ratio of the amount of ionomer to carbon in the catalyst was 9 / 10. The catalyst ink solution was coated on the silicone side of a silicone-coated polyethylene terephthalate (PET) release liner film with a Mayer rod and then dried at 130°C for 10 minutes to form a cathode catalyst layer veneer. The cathode veneer was laminated with the ionomer membrane and the anode veneer to form a CCM as described above. After cell conditioning, the cell was subjected to the catalyst mass activity test protocol as described above. The process was repeated once for each sample, and multiple samples were tested to produce an average value with a standard deviation.

[0207] Example 4

[0208] The cathode veneer was prepared by forming a dispersed catalyst ink composition comprising a carbon-supported catalyst 10V50E and a PFSA-1200 ionomer. The ratio of the amount of ionomer to carbon in the catalyst was 9 / 10. The catalyst ink solution was coated on the silicone side of a silicone-coated polyethylene terephthalate (PET) release liner film with a Mayer rod and then dried at 130°C for 10 minutes to form a cathode catalyst layer veneer. The cathode veneer was laminated with the ionomer membrane and the anode veneer to form a CCM as described above. After cell conditioning, the cell was subjected to the catalyst mass activity test protocol as described above. The process was repeated once for each sample, and multiple samples were tested to produce an average value with a standard deviation. The measured catalyst mass activities of Comparative Example 5 and Example 4 are provided in Table 6 below, showing that Example 4 has greater activity.

[0209] Table 6 .

[0210] IR-corrected mass activity, A / mgPt Standard Deviation Comparative Example 5 0.173 0.029 Example 4 0.269 0.016

[0211] Without departing from the scope and spirit of the present invention, the foreseeable modifications and changes of the present invention will be apparent to those skilled in the art. The present invention should not be limited to the embodiments shown in this application for illustrative purposes. If there is any conflict or contradiction between the disclosure in this specification written and any document incorporated herein by reference, the written specification will prevail.

Claims

1. An at least highly fluorinated ionomer for use in reducing metal catalyst poisoning in an electrochemical cell electrode, wherein the metal catalyst comprises at least one of platinum, ruthenium, iridium, and alloys and combinations thereof; and the at least highly fluorinated ionomer comprises a polymer backbone and a plurality of first side chains pendant from the polymer backbone, wherein the first side chains comprise at least two protogenic groups, wherein each protogenic group is selected from the group consisting of sulfonic acids, bis(sulfonyl)imides, sulfonamides, sulfonyl methides, and salts thereof, and wherein the polymer backbone comprises an average of at least 14 carbon atoms between adjacent first side chains along the polymer backbone.

2. A coating composition, comprising: (a) a metal catalyst, wherein the metal catalyst comprises at least one of platinum, ruthenium, iridium, and alloys and combinations thereof; (b) an at least highly fluorinated ionomer comprising a polymer backbone and a plurality of first side chains pendant from the polymer backbone, wherein the first side chains comprise at least two protogenic groups, wherein each protogenic group is selected from the group consisting of sulfonic acids, bis(sulfonyl)imides, sulfonamides, sulfonyl methides, and salts thereof, and wherein the polymer backbone comprises an average of at least 14 carbon atoms between adjacent first side chains along the polymer backbone; and (c) Solvent.

3. The coating composition according to claim 2, wherein the first side chain is -O-(CF2) m -O-CF-[CF2SO3Y]2, wherein m is 2, 3, 4, 5 or 6; and Y is H or a counterion.

4. The coating composition of claim 2, wherein the at least highly fluorinated ionomer has an equivalent weight of less than 928 g / mol.

5. The coating composition of claim 2, wherein the at least highly fluorinated ionomer has an ionic conductivity of at most 100 mS / cm at 50% relative humidity and 80°C.

6. The coating composition of claim 2, wherein the at least highly fluorinated ionomer comprises at least one bis(sulfonyl)imide and the at least highly fluorinated ionomer has an equivalent weight of at least 350 g / mol.

7. The coating composition of claim 2, wherein the at least highly fluorinated ionomer comprises at least one sulfonic acid or a salt of a sulfonic acid, and the at least highly fluorinated ionomer has an equivalent weight of at least 1100 g / mol.

8. The coating composition of claim 2, wherein the at least highly fluorinated ionomer comprises at least one second side chain, wherein the second side chain is not protogenic, and optionally wherein the second side chain comprises at least one of a perfluorinated alkyl ether, a perfluorinated alkyl polyether, and a perfluorinated alkyl group.

9. The coating composition according to claim 2, wherein the metal catalyst is disposed on a carrier, and optionally, wherein the carrier is at least one of carbon particles, needle-like particles, and a metal organic framework structure.

10. The coating composition of claim 2, wherein the coating composition comprises a mass ratio of the at least highly fluorinated ionomer to the metal catalyst of at least 0.01 to at most 20.

11. The coating composition according to claim 2, wherein the coating composition further comprises an additive, and optionally, wherein the additive is at least one of carbon particles, needle-like particles, and a metal organic framework structure.

12. The coating composition of claim 2, wherein the solvent comprises at least one of an alcohol, a ketone, water, a fluorinated solvent, and combinations thereof.

13. The coating composition of claim 12, wherein the alcohol is a polyol.

14. The coating composition of claim 2, wherein the coating composition comprises 1 wt% to 40 wt% solids.

15. The coating composition of claim 2, wherein the first side chain comprises a plurality of protogenic groups.

16. The coating composition of claim 2, wherein the polymer backbone comprises an average of at least 16 carbon atoms between adjacent first side chains along the polymer backbone.

17. The coating composition of claim 2, wherein the polymer backbone comprises an average of no more than 24 carbon atoms between adjacent first side chains along the polymer backbone.

18. An article containing a metal catalyst phase, the article comprising a substrate having an electrode coating thereon, wherein the electrode coating comprises (a) a metal catalyst phase, wherein the metal catalyst phase comprises at least one of platinum, ruthenium, iridium, and alloys and combinations thereof; and (b) at least a highly fluorinated ionomer layer, the at least highly fluorinated ionomer layer comprising a polymer backbone and a plurality of first side chains pendant from the polymer backbone, wherein the first side chains comprise at least two protogenic groups, wherein each group is a sulfonic acid, a bis(sulfonyl)imide, a sulfonamide, a sulfonyl methide, or a salt thereof, and wherein the polymer backbone comprises an average of at least 14 carbon atoms between adjacent first side chains along the polymer backbone, and optionally wherein the substrate is a gas diffusion layer, a gasket, or an ion conductive membrane.

19. The article of claim 18, wherein the electrode coating has a thickness of at least 0.1 micrometers and at most 100 micrometers.

20. Use of the product according to claim 18: (i) the article is used as a cathode in a fuel cell, wherein the catalyst comprises platinum, or (ii) The article is used as an electrolytic cell, wherein the catalyst does not contain platinum.

Citation Information

Patent Citations

  • Block copolymer, method of making the same, diamine precursors of the same method, method of making such diamines and end products comprising the block copolymer

    EP0250248A2

  • Electrode inks containing coalescing solvents

    US20090169949A1

  • Polymeric electrolyte membrane for a redox flow battery

    US20170365870A1

  • Liners and adhesive tapes having low adhesion polyvinyl carbamate coatings

    US2532011A

  • Epoxypolysiloxane release coatings for adhesive materials

    US4313988A